Analisis Implikasi Undang-Undang No. 17 Tahun 2023 tentang Kesehatan terhadap Praktik Keperawatan di Indonesia - Beatrice Anastasya Secillia A.; Fransiska Sesilia Maranatha; Natalia Ariela Hartanti; Yuniarti, Yuniarti (Jurnal Siti Rufaidah, 2025)
The enactment of Law No. 17 of 2023 on Health marks a significant reform in Indonesia's health legal system, revoking and replacing several previous laws, including Law No. 38 of 2014 on Nursing. This decision carries various implications for nursing practice, particularly concerning professional authority, competency standards, and legal protection for nurses in performing their duties. This study employs a qualitative approach through literature review methods involving legal documents, scientific journals, and expert opinions to analyze the regulatory impact of Law No. 17 of 2023 on the nursing profession. The findings indicate that the new law integrates the role of nurses into a more unified national health service system while formally recognizing the autonomy of nurses as professional healthcare providers. Nevertheless, the repeal of the Nursing Law is considered to create normative gaps, particularly in the technical regulation of nursing practices, ethical codes, and professional sanction mechanisms. This condition highlights the urgency for implementing regulations (government regulations or ministerial decrees) that can adequately accommodate the needs and legal protection of the nursing profession. Therefore, it is essential for stakeholders, including professional organizations and nursing education institutions, to actively engage in responding to these regulatory dynamics. This study is expected to contribute academically to the discourse on the development of health law that is more inclusive of all health professionals, particularly nurses.